Assessment of physicians’ and senior medical students’ knowledge in treatment of patients with community-acquired pneumonia: Current results of the KNOCAP project - Roman A. Bontsevich; Tatiana S. Filinichenko; Anna A. Gavrilova; Natalya Y. Goncharova; Olena V. Myronenko; Olga G. Kompaniets; Elena V. Luchinina; Tatiana M. Shagieva; Oksana G. Ni; Galina G. Ketova; Ekaterina V. Eliseeva; Guzel M. Bikkinina; et al. (Research Results in Pharmacology, 2018)
Introduction. Community-acquired pneumonia (CAP) remains one of the most acute problems of bronchopulmonary pathology being the 4th in the mortality structure (after cardiovascular, cerebrovascular diseases and malignant neoplasms) and the 1st among all fatalities from infectious diseases. Thanks to the scientific progress achieved in the antibiotic therapy and vaccine prophylaxis, the death toll has decreased four times compared to its rate during the “pre-antibiotic era“. However, nowadays there is a steadily increasing trend in the pneumonia mortality rate in Russia. The only possible way to increase efficacy of CAP treatment is timely initiated rational antibiotic therapy, considering the possible etiologies, risk factors and the severity of the patient’s condition.